Carbon black master batch from fresh natural rubber latex - Alex R; Chandra A K; Kurian T; Sasidharan K K (Plastics, Rubber and Composites, 2011)
A new process for the production of carbon black master batches with enhanced mechanical properties has been developed. The unit operations in the process are the preparation of carbon black slurry in the presence of a suitable surfactant, addition of the slurry to the fresh natural rubber (NR) latex under stirring, coagulation of the mixture by the addition of acid, dewatering of the coagulum and drying to obtain carbon black incorporated NR. The competence of the new technique was established by comparing the characteristics of the carbon black incorporated NR by mill mixing process (control). The mechanical properties of the vulcanisates obtained from the latex stage and the dry rubber incorporated mixes were evaluated. The effect of aging on the mechanical properties was also discussed. The carbon black filled mixes prepared by the new process showed better cure characteristics as compared to the dry rubber incorporated mix. The mechanical properties, like tensile strength, modulus, tear strength and hardness, were superior for the vulcanisates prepared by the new method. Comparatively better aging resistance was also recorded by these vulcanisates. The improvement shown by the vulcanisates prepared by the new process was attributed to the better filler dispersion evidenced from the result of filler dispersion data and the scanning electron micrograph studies along with the attainment of a higher level of vulcanisation.
Source Year: 2011
Keywords: Carbon black master batch; Coagulation; Natural rubber latex; Surfactant